Fostering Person Organizing Fit and Psychological Ownership on Creative Behavior Among Indonesian Employees - Helmi Buyung Aulia Safrizal; Indriyani, Ratih (Universitas Islam Lamongan, 2023)
This study focuses on the effect of person organization fit on creative behavior and psychological ownership on creative behavior and the influence of person organization fit on creative behavior with psychological ownership as a mediating variable. Creative behavior is fundamental to produce valuable and innovative products and be able to adapt to customer needs. Creative behavior can support the organization in providing ideas for the progress and sustainability of the organization. Creative produces innovation, both of which play a role in the effectiveness and efficiency of the organization when viewed from the perspective of organizational excellence. This can be said to get creative behavior in the organization, it is necessary to have an employee suitability for the organization, this is an important factor.